mRNA Expression and DNA Methylation of CXCL16 in Menstrual Blood and Endometrium Tissue of Subjects with Endometriosis and Pelvic Pain - Febriyeni, Febriyeni; Hestiantoro, Andon; Tulandi, Togas; Muharam, Muharam; Asmarinah, Asmarinah; Sandra, Ferry (The Indonesian Biomedical Journal, 2024)
BACKGROUND: The cytokine chemokine ligand 16 (CXCL16) plays an important role in the pathophysiology of endometriosis by regulating the inflammatory response and contributing to the pain-associated endometriosis. Despite this, the impact of epigenetic modifications, such as DNA methylation, on CXCL16 has yet to be fully understood. Therefore, this research was conducted to assess both the mRNA expression and DNA methylation levels of the proinflammatory gene CXCL16 in the endometrium tissue and menstrual blood of patients with and without endometriosis.METHODS: Thirty-five women with and without endometriosis were involved in this research. Subjects' menstrual blood samples were collected using filter paper pads, meanwhile the endometrium tissue were collected by performing biopsy, from which DNA and RNA were extracted. The DNA methylation levels of the CXCL16 were measured using the pyrosequencing method following bisulfite conversion treatment. Meanwhile, the mRNA expression level was measured using the quantitative polymerase chain reaction (qPCR) method and analyzed with the Livak method.RESULTS: The mRNA expression of CXCL16 in menstrual blood of endometriosis subjects was 2.42 times higher compared to control group (p=0.030). Furthermore, the expression of CXCL16 in menstrual blood was identical to that in endometrial tissue (p=0.173). DNA methylation analysis showed that CXCL16 in the menstrual blood of endometriosis subjctes had lower methylation levels compared to controls (p=0.004), indicating hypomethylation.CONCLUSION: Increased mRNA expression and hypomethylation of CXCL16 in the menstrual blood of endometriosis patients could serve as a direct marker for diagnosing endometriosis. However, further study to validate these findings and explore the potential of CXCL16 as a diagnostic tool, and additional research involving larger patient for the cohorts study is necessary.KEYWORDS: CXCL16, DNA methylation, endometrium, menstrual blood, mRNA expression, pain